Our World in Data as a resource for teaching Economic History - Puche Gil, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper presents the educational possibilities that the Our World in Data Web has as a teaching resource for the teaching-learning Economic History. Our World in Data, edited by the University of Oxford, is an online publication that based on empirical evidences, analyses and presents complete data on various topics and on a global scale. The paper shows several examples of practices in Economic History from the data of GDP per capita and public social spending provided by the web. It is evident that didactics and online resources cannot be considered incompatible, as they are interconnected.